Perfluorocarbon Emulsion Therapy Attenuates Pneumococcal Infection in Sickle Cell Mice. (26th November 2014) - Helmi, Nawal; Andrew, Peter W.; Pandya, Hitesh C.
Abstract: Impaired immunity and tissue hypoxia-ischemia are strongly linked with Streptococcus pneumoniae pathogenesis in patients with sickle cell anemia. Perfluorocarbon emulsions (PFCEs) have high O2 -dissolving capacity and can alleviate tissue hypoxia. Here, we evaluate the effects of intravenous PFCE therapy in transgenic sickle cell (HbSS) mice infected with S. pneumoniae . HbSS and C57BL/6 (control) mice intravenously infected with S. pneumoniae were treated intravenously with PFCE or phosphate-buffered saline (PBS) and then managed in either air/O2 (FiO2 proportion, 50%; hereafter referred to as the PFCE-O2 and PBS-O2 groups) or air only (hereafter, the PFCE-air and PBS-air groups) gas mixtures. Lungs were processed for leukocyte and bacterial counts and cytokine measurements. HbSS mice developed severe pneumococcal infection significantly faster than C57BL/6 mice (Kaplan–Maier analysis, P < .05). PFCE-O2 –treated HbSS mice had significantly better survival at 72 hours than HBSS mice treated with PFCE-air, PBS-O2, or PBS-air ( P < .05). PFCE-O2 –treated HbSS mice also had significantly lower pulmonary leukocyte counts, lower interleukin 1β and interferon γ levels, and higher interleukin 10 levels than PFCE-air–treated HbSS mice. Clearance of S. pneumoniae from lungs of HbSS mice or C57BL/6 mice was not altered by PFCE treatment. Improved survival of PFCE-O₂–treated HbSS mice infected with S. pneumoniae is associated with altered pulmonary inflammation but not enhanced bacterial clearance.